(untitled) (Bangladesh Journal of Nuclear Medicine, 2016)
Introduction: In cholinergic neurons, high affinity choline uptake (HACU) by the high affinity choline transporter (HAChT) is a rate-limiting and regulatory step for the synthesis of Acetylcholine (Ach).Thus, HAChT appear to be a relatively specific presynaptic marker for cholinergic neurons in Alzheimers disease. Objectives: The principle objective of the study is to check the affinity of tetrahydroaminoacridine (THA) derivatives for HAChT. Another objective of the research work is to clarify whether the hemicholinium-3 (ChT inhibitor) and HACU enhancer molecules share the same binding sites or not. Materials and Methods: The inhibition activities of tacrine, the 2,3-dimethylfuran derivative of tacrine (DMTA) and their corresponding 2-oxo-1-pyrrolidineacetyl derivatives, namely PTAA and MKC-231 were measured by displacement of a typical HAChT antagonist [3H]HC-3 in rat cerebral membrane. The percentage of inhibition against the binding of [3H]HC-3 to HAChT were calculated using GraphPad Prism v4 software. Results: Hemicholinium-3 showed affinity for HAChT (IC50 = 20 nM) in the in vitro binding assay. A very insignificant inhibition activity (IC50 = 1000 nM) of Tacrine was revealed. The newly synthesized tacrine derivatives, DMTA and PTAA did not show any affinity for HAChT. Although MKC-231 was reported to enhance cholinergic activity at synaptic terminals, it did not show any affinity for the HAChT in [3H]HC-3 binding assay. Conclusion: In vitro [3H]HC-3 binding assay revealed no affinity of MKC-231, tacrine and its corresponding2-oxo-1-pyrrolidineacetate derivative towards HAChT. So, it is worthy to develop radiolabeled HC-3 derivatives with high affinity for HAChT, which can diffuse the BBB, to enable the in vivo investigation of HACU system. Bangladesh J. Nuclear Med. 17(2): 97-102, July 2014